Ethanol Dehydrogenation to Acetaldehyde over Activated Carbons-Derived from Coffee Residue - Jeerati Ob-eye; Piyasan Praserthdam; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
This study focuses on the production of acetaldehyde from ethanol by catalytic dehydrogenation using activated carbon catalysts derived from coffee ground residues and commercial activated carbon catalyst. For the synthesis of activated carbon catalysts, coffee ground residues were chemical activated with ZnCl2 (ratio 1:3) followed by different physical activation. All prepared catalysts were characterized with various techniques such as nitrogen physisorption (BET and BJH methods), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), temperature programmed desorption (CO2-TPD and NH3-TPD), X-ray Difraction (XRD), Fourier transform infrared spectrometer (FT-IR), and thermogravimetric analysis (TGA). The dehydrogenation of vaporized ethanol was performed to test the catalytic activity and product distribution. Testing catalytic activity by operated in a fixed-bed continuous flow micro-reactor at temperatures ranged from 250 to 400 °C. It was found that the AC-D catalyst (using calcination under carbon dioxide flow at 600 °C, 4 hours for physical activation) exhibited the highest catalytic activity, while all catalysts show high selectivity to acetaldehyde (more than 90%). Ethanol conversion apparently increased with increased reaction temperature. At 400 ºC, the AC-D catalyst gave the highest ethanol conversion of 47.9% and yielded 46.8% of acetaldehyde. The highest activity obtained from AC-D catalyst can be related to both Lewis acidity and Lewis basicity because the dehydrogenation of ethanol uses both Lewis acid and Lewis basic sites for this reaction. To investigate the stability of catalyst, the AC-D catalyst showed quite constant ethanol conversion for 10 h. Therefore, the synthesized activated carbon from coffee ground residues is promising to be used in dehydrogenation of ethanol.